Moving Beyond Fidelity: Assessing Implementation of a Comprehensive Treatment Program for Adolescents With Autism Spectrum Disorder. (January 2020) - Steinbrenner, Jessica R.; Odom, Samuel L.; Hall, Laura J.; Hume, Kara
Assessing implementation of comprehensive treatment programs is a multifaceted process that should extend beyond measuring solely treatment fidelity. The purpose of this article is to describe and demonstrate a thorough process for assessing implementation and receipt of a comprehensive treatment program for students with autism spectrum disorders in high schools. The Center on Secondary Education for Students With Autism Spectrum Disorders (CSESA) developed a profile and index approach to assess implementation of seven features related to the CSESA intervention process and content. In a cluster-randomized trial, the CSESA implementation profile captured information about diverse features of implementation, and this index successfully differentiated between intervention and control schools. A multifeatured implementation profile and index is an important step forward for examining and implementing comprehensive treatment programs in educational settings.